Otitis Media and Internal with Brainstem Extension in a French Bulldog - Lopes, Matheus Garcia; Soares, Fernanda de Oliveira; Alves, Endrigo Gabellini Leonel; Rosado, Isabel Rodrigues (Acta Scientiae Veterinariae, 2021)
Background: Otitis is a frequent condition in dogs, with a multifactorial etiology covering primary causes, predisposing and perpetuating factors. It is characterized by an inflammatory process of structures that make up the auditory system, with prevalence data ranging from 15 to 20%, which can occur in any age group and without sex predisposition. According to the location, it can be classified as uni or bilateral, affecting the outer, middle and / or inner ear, the latter two being associated with neurological changes such as vestibulopathy, facial nerve paresis and Horner's syndrome. The morbidity and mortality of otitis media and internal may increase with delay in diagnosis, resulting in delay in the correct treatment, and the extension to brainstem is described in felines and considered rare in dogs. The present study aims to report an atypical case of otitis media and internal, with extension to the brain parenchyma in a brachycephalic dog. Case: A 3-year-old bitch French Bulldog canine was seen, weighing 12 kg, with a history of vomiting, apathy, nystagmus, ataxia and acute evolution hemiparesis. As a result of adoption, it was not known about the animal's morbid past. On special physical and clinical examination, depressed mental status, changes in postural reactions, nostril stenosis with unilateral mucopurulent nasal discharge, corneal ulcer, palpebral and labial ptosis, absence of eyelid reflex and spontaneous strabismus were observed, all of these findings observed on the left side of the face. No signs of otitis external to otoscopy were found. The clinical signs found characterize left facial nerve paresis and peripheral and central vestibulopathy. Otitis media / internal and meningoencephalitis were suspected. Hemogram, serum biochemistry (glucose, urea, creatinine, alanine aminotransferase, total proteins, albumin, globulin, alkaline phosphatase, gamma glutamyltransferase, phosphorus, total bilirubin, cholesterol and total calcium), urinalysis, rapid tests for erlichiosis, anaplasms , borreliosis, heartworm, distemper and leishmaniasis, CSF analysis, neurological panel performed by PCR (Polymerase Chain Reaction) that tested the animal for Bartonellosis, Lyme Disease (Borrelia burgdorferi), Blastomyces dermatitidis, Cryptococcus sp., Virus West Nile, Distemper, Toxoplasmosis, Neosporose and Coccidioides sp. using conjunctival swab, whole blood, urine and CSF samples. The samples were negative for all of these tests. As an image exam, brain magnetic resonance was performed. In the latter, otitis media and left internal was observed with extension of the lesion to the brain parenchyma. CSF analysis showed cytological changes compatible with a non-suppurative inflammatory process, mild pleocytosis with predominantly mononuclear leukocyte infiltrate. As a form of treatment, antibiotic therapy and total ablation of the auditory canal with lateral bulectomy were performed, showing good results with reduced clinical symptoms. Discussion: It is concluded that although the diagnosis of otitis media and internal with extension to brainstem is more common in cats, it should be included as a differential for central vestibular disorders in dogs, and that the diagnosis together with early and effective treatment are important, since that the evolution of the infection to the central nervous system represents a risk to the patient. Keywords: vestibulopathy, meningoencephalitis, brachycephalic. Descritores: vestibulopatia, meningoencefalite, braquicefálico. Título: Otite média e interna com extensão para tronco encefálico em cão buldogue francês